The Influence of Training, Entrepreneurship Education and Motivation on Technopreneur Interest among the Gen Z Generation - Muhammad Randika Agusti Syah Putra; Muhammad Kosim; Adibah Yahya (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
This study aims to analyze the influence of entrepreneurial training, entrepreneurial education, and motivation on technopreneurial interest among Generation Z. A quantitative approach was employed using multiple linear regression analysis. The respondents consisted of 100 individuals from Generation Z. The results indicate that entrepreneurial training does not have a statistically significant effect on technopreneurial interest, with a significance value of 0.081 (> 0.05) and a regression coefficient of 0.238. In contrast, entrepreneurial education shows a highly significant influence with a significance value of 0.000 and a regression coefficient of 0.556. Furthermore, entrepreneurial motivation also significantly influences technopreneurial interest, with a significant value of 0.002 and a regression coefficient of 0.240. Therefore, it can be concluded that entrepreneurial education and motivation are key factors that drive Generation Z's interest in becoming technopreneurs, while training has not yet made a statistically significant contribution.